2017
DOI: 10.1155/2017/6710278
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Role of Neutrophils in Common Respiratory Diseases

Abstract: Respiratory diseases, always being a threat towards the health of people all over the world, are most tightly associated with immune system. Neutrophils serve as an important component of immune defense barrier linking innate and adaptive immunity. They participate in the clearance of exogenous pathogens and endogenous cell debris and play an essential role in the pathogenesis of many respiratory diseases. However, the pathological mechanism of neutrophils remains complex and obscure. The traditional roles of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 236 publications
(273 reference statements)
2
72
0
2
Order By: Relevance
“…Upregulation of neutrophil chemoattractors (LTB 4 , CXCL1, CXCL5, IL-8, and TNF-α) induces a massive migration of circulating neutrophils into the lung parenchyma ( 96 ). The transmigration of blood neutrophils occurs through adherence of the granulocytes to E-selectin of endothelial cells that is found to be upregulated in COPD ( 97 ).…”
Section: Alteration Of Airway Gene Expression and Immune Response In mentioning
confidence: 99%
“…Upregulation of neutrophil chemoattractors (LTB 4 , CXCL1, CXCL5, IL-8, and TNF-α) induces a massive migration of circulating neutrophils into the lung parenchyma ( 96 ). The transmigration of blood neutrophils occurs through adherence of the granulocytes to E-selectin of endothelial cells that is found to be upregulated in COPD ( 97 ).…”
Section: Alteration Of Airway Gene Expression and Immune Response In mentioning
confidence: 99%
“…In particular, this review will focus on the shared role of the neutrophil in these diseases. While neutrophils are not the only cells that play a role in COPD, atherosclerosis and T2D, they are the most abundant immune cells found in lung secretions of patients diagnosed with COPD and their products have been shown to cause all facets of lung disease in animal and cell models (from chronic bronchitis to emphysema); correlating with disease severity and decline [19,20]. Recent advances in imaging technologies have also identified that neutrophils are present in the lipid core of human plaques and neutrophilia correlates with the number of rupture-prone lesions [21] and, although less studied, diabetic patients, rats and mice clearly demonstrate consistent defects of neutrophil chemotactic, phagocytic and microbicidal activities [22].…”
Section: Introductionmentioning
confidence: 99%
“…IL-6 can mediate both pro-inflammatory and anti-inflammatory functions [ 138 ]. An acute increase in IL-6 facilitates neutrophil recruitment to sites of tissue injury in order to induce acute inflammation [ 143 ]. However, IL-6 also activates STAT3 signaling which facilitates the reduction in neutrophils in acute inflammation [ 144 ].…”
Section: Deficiency In Cell Signaling Molecules As Determinants Ofmentioning
confidence: 99%